Synthesis of α‐Propargylglycinates Using the Borono‐Mannich Reaction with Pinacol Allenylboronate and Potassium Allenyltrifluoroborate. Issue 22 (14th July 2016) - Chambers, Rachel K.; Chaipukdee, Nattapong; Thaima, Thanaphat; Kanokmedhakul, Kwanjai; Pyne, Stephen G.
Abstract : The three component borono‐Mannich reactions of ethyl glyoxylate, primary or secondary amines and pinacol allenylboronate or potassium allenyltrifluoroborate are highly regioselective and give α‐propargylglycinates. The ( S )‐ N ‐ tert ‐butylsulfinyl imine of ethyl glyoxylate underwent an indium chloride catalyzed addition reaction with allenyl potassium trifluoroborate in a highly regioselective and diastereoselective manner to give ethyl ( S )‐α‐propargylglycinate after N ‐deprotection in 97 % ee . Abstract : A regioselective synthesis of α‐propargylglycinates using the borono‐Mannich reaction has been developed.